Relations entre les cadres de l’expérience dans le discours — exemple du fait divers - Miczka, Ewa (Neophilologica, 2011)
In this paper the author analyzes situational structures of discourse which are defined as a sequence of experiential frames (E. Goffman, 1991). Each frame makes it possible to conceptualize one event as forming a part of information introduced in discourse. Analyzing the possible relations between frames in discourse, the author aims to indicate their role in discourse comprehension — a process which implicates creation of discourse representation.